Depletion of Human Papilloma Virus E6- and E7-Oncoprotein-Specific T-Cell Responses in Women Living With HIV - Mbuya, Wilbert; Held, Kathrin; Mcharo, Ruby D.; Haule, Antelmo; Mhizde, Jacklina; Mnkai, Jonathan; Mahenge, Anifrid; Mwakatima, Maria; Sembo, Margareth; Mwalongo, Wolfram; Agrea, Peter; Hoelscher, Michael; et al. (Frontiers in Immunology, 2021)
Background Cervical cancer - caused by persistent High Risk Human Papilloma Virus (HR HPV) infections - is the second most common cancer affecting women globally. HIV infection increases the risk for HPV persistence, associated disease progression and malignant cell transformation. We therefore hypothesized that this risk increase is directly linked to HIV infection associated dysfunction or depletion of HPV-oncoprotein-specific T-cell responses. Methods The 2H study specifically included HIV+ and HIV- women with and without cervical lesions and cancer to analyze HPV oncogene-specific T cell responses in relation to HPV infection, cervical lesion status and HIV status. Oncoprotein E6 and E7 specific T-cell responses were quantified for the most relevant types HPV16, 18 and 45 and control antigens (CMV-pp65) and M.tb-PPD in 373 women, using fresh peripheral blood mononuclear cells in an IFN-γ release ELISpot assay. Results Overall, systemic E6- and E7-oncoprotein-specific T-cell responses were infrequent and of low magnitude, when compared to CMV-pp65 and M.tb-PPD (p < 0.001 for all HR HPV types). Within HIV negative women infected with either HPV16, 18 or 45, HPV16 infected women had lowest frequency of autologous-type-E6/E7-specific T-cell responses (33%, 16/49), as compared to HPV18 (46% (6/13), p = 0.516) and HPV45 (69% (9/13), p = 0.026) infected women. Prevalent HPV18 and 45, but not HPV16 infections were linked to detectable oncoprotein-specific T-cell responses, and for these infections, HIV infection significantly diminished T-cell responses targeting the autologous infecting genotype. Within women living with HIV, low CD4 T-cell counts, detectable HIV viremia as well as cancerous and precancerous lesions were significantly associated with depletion of HPV oncoprotein-specific T-cell responses. Discussion Depletion of HPV-oncoprotein-specific T-cell responses likely contributes to the increased risk for HR HPV persistence and associated cancerogenesis in women living with HIV. The low inherent immunogenicity of HPV16 oncoproteins may contribute to the exceptional potential for cancerogenesis associated with HPV16 infections.